Measurement report: Large contribution of biomass burning and aqueous-phase processes to the wintertime secondary organic aerosol formation in Xi'an, Northwest China - J. Duan; R.-J. Huang; R.-J. Huang; R.-J. Huang; R.-J. Huang; Y. Gu; Y. Gu; C. Lin; H. Zhong; H. Zhong; W. Xu; Q. Liu; et al. (Atmospheric Chemistry and Physics, 2022)
Secondary organic aerosol (SOA) plays an important role in particulate air pollution, but its formation mechanism is still not fully understood. The chemical composition of non-refractory particulate matter with a diameter ≤2.5 µm (NR-PM2.5), OA sources, and SOA formation mechanisms were investigated in urban Xi'an during winter 2018. The fractional contribution of SOA to total OA mass (58 %) was larger than primary OA (POA, 42 %). Biomass-burning-influenced oxygenated OA (OOA-BB) was resolved in urban Xi'an and was formed from the photochemical oxidation and aging of biomass burning OA (BBOA). The formation of OOA-BB was more favorable on days with a larger OA fraction and higher BBOA concentration. In comparison, the aqueous-phase processed oxygenated OA (aq-OOA) was more dependent on the secondary inorganic aerosol (SIA) content and aerosol liquid water content (ALWC), and it showed a large increase (to 50 % of OA) during SIA-enhanced periods. Further van Krevelen (VK) diagram analysis suggests that the addition of carboxylic acid groups with fragmentation dominated OA aging on reference days, while the increased aq-OOA contributions during SIA-enhanced periods likely reflect OA evolution due to the addition of alcohol or peroxide groups.